Contract Agreement Between New Mexico State Park & Recreation Commission Bicentennial Division and City of Raton, New Mexico (New Mexico State Park and Recreation Commission, 1974)
This a legal agreement between the New Mexico State Park and Recreation Commission Bicentennial Division and City of Raton, New Mexico for the Colfax County Historical Museum Development, Project number 47-13PM-73 approved date March 20, 1974 expiration date December 31, 1976.
Legal Document
Master list item #: 71
File location is in the Raton file Cabinet
Keywords: New Mexico State Park and Recreation Commission Bicentennial Division; City of Raton; Establish Historical Museum; Museum Contracts; Museum Business; Contract Outline; Museum Finances; Raton, New Mexico